Assessment of muttukadu lake water quality in Terms of water quality index & Regression Analysis of water quality parameters - M , Tholkapiyan; S. , Mohammad Zubair (International Journal of Psychosocial Rehabilitation, 2020)
In today’s industrial societies, necessities for water—quite a bit of which is gotten from lakes—incorporate its utilization for weakening and expulsion of cities and modern squanders, requirements include. The lake water is normally used for agricultural purposes; it is also used for dilution and elimination of municipal and industrial wastes, for irrigation, for energy technology, and for local undertakings and aesthetic displays. However, the contaminated water produced by the ventures and homes that are not appropriately treated gets cycled once again into lakes, bringing about the contamination of lakes. The present study manages the assurance of water quality list based on Weighted Arithmetic Index by contemplating different Total hardness, Electrical Conductivity, total alkalinity, Total Dissolved Solids, Magnesium and Calcium particles, and so on to survey the water quality and phyico-parameters of Muttukadu Lake.